A revision of the Rutilus complex from Mediterranean Europe with description of a new genus, Sarmarutilus, and a new species, Rutilus stoumboudae (Teleostei: Cyprinidae) - Bianco, Pier Giorgio; Ketmaier, Valerio (Zootaxa, 2014)
By combining morphology, ecology, biology, and biogeography with the available molecular (sequence variation of the entire mitochondrial cytochrome b gene; cyt-b) and karyology data, the taxonomy of several species of the Rutilus complex inhabiting southern Europe is revised. Rutilus stoumboudae, new species, is described from Lake Volvi, Greece. It differs from Rutilus rutilus in possessing more total GR and less branched rays in both dorsal and anal fins and in its placement in the cyt-b based phylogeny of the genus. The resurrected genus Leucos Heckel, 1843 (type species Leucos aula, Bonaparte, 1841), which according to molecular data diverged from Rutilus more than 5 million years ago, during the Messinian salinity crisis, includes five species of small size, without spinous tubercles on scales and head in reproductive males, pharyngeal teeth formula 5-5, and all show a preference for still waters. Leucos aula is the Italian species endemic in the Padany-Venetian district: L. basak is widespread in Croatia, Albania, Montenegro and former Yugoslav Republic of Macedonia (FYROM); L. albus, recently described from Lake Skadar, Montenegro, is also found in rivers Moraca and Zeta (Montenegro). L. albus differs from L. basak, its closest relative, in having more scales on the LL and less anal-fin rays; L. panosi is endemic to the western-Greece district, and L. ylikiensis is endemic to lakes Yliki and Paralimni in eastern Greece (introduced in Lake Volvi). Among the nominal species examined, Rutilus karamani, R. ohridanus, R. prespensis and R. prespensis vukovici are all junior synonyms of Leucos basak. Rutilus vegariticus is definitively regarded as junior synonym for R. rutilus. Sarmarutilus n.gen. is a monotypic genus, with Sarmarutilus rubilio as the type species. According to phylogenetic data, Sarmarutilus rubilio is basal to a cluster of species that includes Leucos basak, L. albus, L. aula, L. panosi and L. ylikiensis. Sarmarutilus possibly evolved in pre-Messinian time, in the Lago Mare, entered the Mediterranean area during the Messinian Lago Mare phase of the Mediterranean Sea and survived only in the Tuscany- Latium district. This genus differs from Leucos in having large pearl organs on the central part of head and body scales in mature males and for the habitat preference, being a riverine-adapted species. It differs from Rutilus in pharyngeal teeth formula (5-5 in Sarmarutilus and 6-5 in Rutilus), size (small in Sarmarutilus and large in Rutilus) and for the preferential habitat (riverine vs. still water). Finally, lectotypes for Leucos basak, Leucos aula, and Sarmarutilus rubilio are designated.